The Evolution of Inequality in Education Trajectories and Graduation Outcomes in the US - Christian Belzil; Jörgen Hansen; Xingfei Liu (Institute of Labor Economics (IZA), 2022)
We model the joint distribution of (i) individual education trajectories, defined by the allocation of time (semesters) between various combinations of school enrollment with different labor supply modalities and periods of school interruption devoted either to employment or home production and (ii) actual graduation outcomes using two cohorts of the National Longitudinal Survey of Youths which we follow from 16 to 28. We discuss the evolution of family income and ability effects where the latter are decomposed into an academic (cognitive) and a practical (technical-mechanical) latent ability factor component correlated with family income and background variables. We find that the individual cognitive-technical ability differential prevailing at 16 was increasing with income in the early 80's but much less so in the early 2000's. We find no evidence of any income-based "trajectory inequality" in either cohort, after conditioning on abilities. Among all graduation and enrollment outcomes, college graduation is the only for which the effect of income has increased between the 1980's and the early 2000's but it reached a level no more important than the high school graduation income effect. In both cohorts, cognitive and technical abilities were the dominant factors but they affect most dimensions of individual trajectories and all graduation outcomes in opposite directions. However, the cognitive ability factor lost half of its effect on college graduation while the impact of the technical-mechanical factor has been more stable across cohorts.
Keywords: I2; J1; J3; 330; education; inequality; family income; multi-dimensional abilities; labor supply